PARAMETER POPULASI IKAN TERI PUTIH (Stolephorus indicus) DI TELUK AMBON BAGIAN D ALAM [Population parameters of indian anchovy, Stolephorus indicus in inner Ambon Bay] - OTS Ongkers (Jurnal Iktiologi Indonesia, 2008)
Over a 12 months period (August 2005 - July 2006), population parameters of Indian anchovy (Stolephorus indicus) in the Inner Ambon Bay was evaluated. The objectives of the present study were to determine the population parameters (growth, recruitment pattern and mortality) of Indian anchovy. Result showed that growth parameters (L”, K. and tj were 12.18 cm, 1.3 and -0.07 year, respectively; the recruitment pattern showed two pulses with two peaks, occuring in March and July; the mortality (Total, Natural and Fishing) were 5.78, 2.73 and 3.05 respectively. These parameters indicated that the Indian anchovy was overfished or over exploited (0.53).